Global capital, global labour and global dominance: The case of xXx: Return of Xander Cage. (1st March 2019) - Koushik, Kailash; Proffitt, Jennifer M.
This article analyses the movie, xXx: Return of Xander Cage, produced to attract global audiences and increase global investments in Hollywood, by examining its production, financing, marketing and distribution practices. The aim of this article is to point to a shift in the way in which global Hollywood operates, exploits and maintains its economic and cultural dominance. It explores Return of Xander Cage as a case study of how particular Hollywood films are now being produced for the influential Chinese and Indian markets by using the resources of the target nations to counter competition from these same markets.